KOMPONEN KURIKULUM DAN LANGKAH-LANGKAH PENGEMBANGANNYA PADA PENDIDIKAN AGAMA ISLAM - Nabil Tito Prasetyo; Agus Pahrudin, Agus Jatmiko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of an Islamic Religious Education (PAI) curriculum is a fundamental aspect in producing a generation that is not only intellectually intelligent but also imbued with noble character in accordance with national education goals. The curriculum is viewed as a strategic tool that guides students in the learning process toward spiritual, cognitive, affective, and psychomotor competencies. This article discusses the basic concepts, components, and steps in developing an Islamic Religious Education (PAI) curriculum that is oriented towards values, social relevance, and the needs of students in the modern era. The analysis shows that the development of the PAI curriculum emphasizes the integration of national education goals, Islamic principles, and implementation strategies that are contextualized to the socio-cultural conditions of society. Thus, the PAI curriculum functions not only as a tool for transmitting knowledge but also as an instrument for character formation and social ethics in everyday life.